2022
DOI: 10.1111/jpi.12797
|View full text |Cite
|
Sign up to set email alerts
|

The phytomelatonin receptor PMTR1 regulates seed development and germination by modulating abscisic acid homeostasis in Arabidopsis thaliana

Abstract: Melatonin is known to involve multiple physiological actions in plants. Herein, we found that exogenous melatonin inhibited the Arabidopsis seedling growth through the elevated abscisic acid (ABA) levels, and the elevated ABA was ascribed to the upregulation of 9‐cis‐epoxycarotenoid dioxygenase genes (NCEDs) in the ABA biosynthesis pathway. We also found that the overexpression lines of the melatonin receptor gene PMTR1 (also known as Cand2) yielded smaller seeds and germinated slower than the wild type, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 58 publications
0
36
0
Order By: Relevance
“…Several studies have found that melatonin can promote seed germination under stress conditions, especially in old or damaged seeds, improving germination rate probably through fit hormonal balance ( K. Wang et al , 2022 ). In contrast, Lv et al (2021) and Yin et al (2022) have shown that high concentrations of melatonin inhibit Arabidopsis seed germination and seedling growth, possibly due to disorder in ABA, GA, and auxin balance. It is interesting that PMTR1 -knockout mutants contain higher ABA concentrations in developing seeds, but accumulate lower ABA contents in dry and imbibed seeds than the wild-type Col-0 ( Yin et al , 2022 ), indicating that PMTR1 is involved in phytomelatonin-mediated seed development, dormancy, germination, and seedling growth via crosstalk with ABA signaling.…”
Section: Phytomelatonin Signaling In Plant Growth and Developmentmentioning
confidence: 94%
See 3 more Smart Citations
“…Several studies have found that melatonin can promote seed germination under stress conditions, especially in old or damaged seeds, improving germination rate probably through fit hormonal balance ( K. Wang et al , 2022 ). In contrast, Lv et al (2021) and Yin et al (2022) have shown that high concentrations of melatonin inhibit Arabidopsis seed germination and seedling growth, possibly due to disorder in ABA, GA, and auxin balance. It is interesting that PMTR1 -knockout mutants contain higher ABA concentrations in developing seeds, but accumulate lower ABA contents in dry and imbibed seeds than the wild-type Col-0 ( Yin et al , 2022 ), indicating that PMTR1 is involved in phytomelatonin-mediated seed development, dormancy, germination, and seedling growth via crosstalk with ABA signaling.…”
Section: Phytomelatonin Signaling In Plant Growth and Developmentmentioning
confidence: 94%
“…In contrast, Lv et al (2021) and Yin et al (2022) have shown that high concentrations of melatonin inhibit Arabidopsis seed germination and seedling growth, possibly due to disorder in ABA, GA, and auxin balance. It is interesting that PMTR1 -knockout mutants contain higher ABA concentrations in developing seeds, but accumulate lower ABA contents in dry and imbibed seeds than the wild-type Col-0 ( Yin et al , 2022 ), indicating that PMTR1 is involved in phytomelatonin-mediated seed development, dormancy, germination, and seedling growth via crosstalk with ABA signaling. Transgenic Arabidopsis plants overexpressing AtPMTR1 produce smaller seeds and germinate more slowly than Col-0 plants ( Yin et al , 2022 ).…”
Section: Phytomelatonin Signaling In Plant Growth and Developmentmentioning
confidence: 94%
See 2 more Smart Citations
“…Melatonin ( N ‐acetyl‐5‐methoxytryptamine) is an endogenous micromolecular indoleamine compound that has multiple physiological functions in various organisms (Zhang & Zhang, 2021), and the identification of phytomelatonin receptor 1 (PMTR1) has been a turning point for understanding phytomelatonin functions (Wang et al, 2021; Wei et al, 2018; Yin et al, 2022). Phytomelatonin not only plays an important role in regulating plant growth and development (Arnao & Hernández‐Ruiz, 2020; Li et al, 2022) but is also a well‐known antioxidant that improves plant tolerance to various abiotic stresses (Arnao & Hernández‐Ruiz, 2019; Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%